PERANAN NEUROHORMONAL DALAM NEUROINFLAMASI PADA STROKE ISKEMIK AKUT - Felicia Theddy; Fadila Olivia; Sang Ayu Nyoman Putri Pradnyasari; Ilsa Hunaifi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
Stroke is the second most common cause of death and the third most common cause of disability in the world. Globally, 68% suffer from ischemic stroke. Post-ischemic stroke occurs a neuroinflammatory process which is a natural response of the immune system to tissue ischemia. The inflammatory process develops into three phases, namely the acute phase which begins shortly after the ischemic stroke, the subacute phase which begins several days after the ischemic stroke, and the final phase of astrocyte and microglia recovery. Neuroinflammation is a complex process involving inflammatory cells, inflammatory mediators, and hormones. Hormones that play a role in the neuroinflammatory process either increase or decrease the inflammatory response, namely estrogen, progesterone, testosterone, oxytocin, glucocorticoids, and cortisol.